Communication Through Music During the Attack of Covid-19 (Journal of Namibian Studies : History Politics Culture, 2023)
Precisely December 2019, the pandemic or Corona virus 2019 was first identified in the city of Wuhan in China. Since then, more than 100 million people have been detected by the virus, which WHO states are because it has spread to more than 215 countries. Covid has increased its impact on health and all music business and education, so it has impacted the decline of musical activity. During the pandemic, various studies have been carried out, but few have studied music communication which can be categorized as education. This was a qualitative study using secondary data, especially from books and international journal articles that discussed music and pandemic issues. There are four types of data that have been successfully collected, including data on physical benefits, data on music communication, the benefits of criticism during a pandemic, and also the role of music in preventing pandemics. I then examine the data and discuss the results where we see that music has a huge opportunity to continue despite a pandemic. Because in this revolutionary era, music can be enjoyed without having to interact, like on stage and in concerts in buildings because of the technological era people who enjoy music. Finally, it can concluded that the music is played to socialize the dangers of the pandemic and prevention efforts. The use of music to socialize and raise public awareness of the pandemic is very effective here. One example is what government and other world bodies in Vietnam did with a song themed "Ghen Cô Vy".